Self-interference in Multi-tap Channels for Full-Duplex Wireless Systems - Sabah, Ayman T. Abu (2020)
Residual self-interference (SI) is primarily a key challenge when designing In-Band Full-duplex (IBFDX) wireless systems. Channel estimation errors are one of the major causes of residual SI. Consequently, a deeper understanding of the impact of the channel effects on the residual SI becomes indispensable. In this paper, we investigate the influence of multiple taps on the residual SI power of IBFDX systems. We first formulate the effect of having independent taps on the residual SI power mathematically. The derivations take into account the amount of interference cancellation on each tap by considering phase and amplitude estimation coefficients. We conclude that the increase in the number of taps always leads to an additive effect of the residual power. Such findings are shown mathematically and also reported in different results obtained by simulation. Finally, we compare the distribution of the residual SI power with different known distributions, concluding that Weibull and Gamma distributions are the closest ones in terms of accuracy. In-Band Full-Duplex communication Residual self-interference Independent fading taps channel.